PENGARUH KEGIATAN EKSTRAKURIKULER PRAMUKA TERHADAP KEDISIPLINAN PESERTA DIDIK DI SDN 06 JAMBU DESA BERINGIN KECAMATAN SAJAD - Muhammad Wildani; Parni Parni (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2018)
The purpose of this research is to reveal about: 1) scout extracurricular activities at 06 Jambu school year 2019-2020. 2) discipline of students in 06 Jambu school year 2019-2020. 3) influence of scout extracurricular activities towards discipline of students in 06 Jambu school year 2019-2020. This study uses a quantitative approach and type of associative research. Data collection techniques using direct communication techniques, indirect communication techniques, and documentation. The data analysis technique used is descriptive statistics, Pearson product moment correlation, linear regression. The results showed that: Scout extracurricular activities are classified as